Red Kites Milvus milvus wintering in their natal area: demographic, environmental, and temporary factors affecting spatiotemporal behaviour patterns. Issue 3 (3rd July 2021) - Škrábal, Jan; Literák, Ivan; Dostál, Marek; Raab, Rainer; Horal, David; Matušík, Hynek; Spakovszky, Péter
ABSTRACT: Capsule: Some birds of the central European population of Red Kite Milvus milvus are non-migratory and winter within their natal area, whereas others migrate to southern Europe or even to northern Africa. Aims: To determine what factors affect the area use and communal roost use by Red Kites wintering in their natal area. Methods: We studied spatiotemporal activity and factors affecting area use by Red Kites wintering in their natal area in the tripoint border area of Austria, the Czech Republic, and Slovakia, using GPS/GSM telemetry devices. Results: We characterized home ranges used by wintering Red Kites in natal areas. Birds wintered for an average of 146 days and spent 88% of the time within temporary settlement areas (TSAs). The number of TSAs used by one Red Kite during the winter varied from 1–4 (mean ± sd = 2 ± 1); the mean (± sd) size of the home range of TSAs was 190 ± 144 km 2 as a 95% minimum convex polygon, 136 ± 82 km 2 as a 95% kernel density estimate, and 41 ± 34 km 2 as a 50% kernel density estimate (core activity area). Age, breeding status, and percentage of forest habitat were the main factors negatively related to home range size. Winter duration and the number of TSAs were positively related to the size of the home range. Young birds (before first breeding) and males explored larger areas and used more TSAs during winter. Conclusion: Wintering of Red Kites in their natal area may relate to the social refuge–territory prospecting hypothesis, breeding site fidelity, wintering site fidelity, and/or mate loyalty, and this understanding could lead to better conservation of Red Kites in central Europe.